15. Polonaise for Violin and Piano OP. 4 in d Major by Henryk Wieniawski - Ioniță Raluca Dobre (Sciendo, 2022)
Wieniawski's creations for violin imposed themselves in the romantic musical literature both by their special melodic musicality and by the difficulty of the technical passages. Polonaise for violin and piano, op. 4 in D major is one of the most beautiful musical jewels of the romantic century. The piece has become famous since the time of the composer, who performed it quite frequently in his tours. In this composition, Wieniawski emphasizes to the maximum the timbre, technical and interpretive potential of the violin.